Investigation on the interaction between lysozyme and cefepime hydrochloride by synchronous fluorescence and fluorescence quenching spectroscopy. Issue 3 (15th March 2016) - Han, Rong; Liu, Bao-sheng; Li, Gaixia; Zhang, Qiuju
ABSTRACT: The interaction between cefepime hydrochloride and lysozyme at different temperatures was investigated using fluorescence quenching and synchronous fluorescence spectroscopy. The results demonstrated that the interaction between lysozyme and cefepime hydrochloride was taking place via static quenching with 1:1 binding ratio. The binding constants obtained from the above method were of the same order of magnitude and very similar. The electrostatic interaction played a key role during the binding process. In addition, the conclusions obtained from the two methods were consistent. It indicated that the synchronous fluorescence spectrometry could be used to study the binding mechanism between drugs and lysozyme.